Prevalence and potential factors associated with probable sleep or awake bruxism and dentin hypersensitivity in undergraduate students - Neusa Barros DANTAS-NETA; Joseany Barbosa LAURENTINO; Carlos Henrique de Carvalho e SOUZA; Danila Lorena NUNES-; Regina Ferraz MENDES; Raimundo Rosendo PRADO-JÚNIOR
OBJECTIVE: To measure the prevalence of probable sleep or awake bruxism and cervical dentin hypersensitivity of undergraduate students and to determine the symptoms associated with these conditions.METHODOLOGY: This was a cross-sectional study. A diagnosis of probable bruxism was reached when students reported clenching or grinding of the teeth during sleep and/or wakefulness, and when they also presented some of the signs and symptoms of bruxism and masseter muscle pain on palpation. Cervical dentinal hypersensitivity was diagnosed by testing for sensitivity to pain in the cervical region of the teeth. Pain was triggered either by touch (using a #5 probe) or by an air jet spray. The sample consisted of 306 university students aged between 19 and 35 years old. The data were stored and analysed using SPSS software, version 15.0 for Windows.RESULT: The prevalence of probable bruxism was 34.3%, with no predominance regarding sex. Probable awake bruxism was more prevalent (61.9%), mostly occurring when the individual reported being in a state of mental concentration (63.1%). There was no association between probable sleep or awake bruxism and dentin hypersensitivity (p = 0.195). Individuals with probable sleep bruxism had increased odds of having muscular pain in the face upon waking (OR = 14.14, 95% CI 5.06-39.55), and those with probable awake bruxism had a increased odds of having facial muscle fatigue when chewing or talking for a long time (OR = 2.88, 95% CI 1.53-5.43) and muscular pain in the face upon waking (OR = 5.31, 95% CI 1.93-14.62).CONCLUSION: The prevalence of probable bruxism was 34.3% and that of HDC was 57.8%, with 22.2% of these subjects also showing probable bruxism. Individuals with probable bruxism tended to have a higher odds of facial pain when they awakened and when chewing or talking for long periods. There were no associations between probable sleep and awake bruxism and cervical dentin hypersensitivity.